Research Progress in Inhibiting Tumor Cells Through Sugar Metabolism in the TME - Chen, Yiwen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In the immune microenvironment, the sugar metabolism of tumor cells determines their own growth, and the disturbance of metabolic process is considered as an important feature of tumor cell growth. Compared with normal cells, the greatest change in the metabolic process of tumor cells is the occurrence of aerobic glycolysis. Even under sufficient oxygen conditions, tumor cells will still absorb a lot of glucose through glycolysis to provide energy for cells, and many important rate-limiting enzymes in the glycolysis process are expressed in different forms in tumor cells and have an important impact on tumor growth. However, the specific mechanism of this conversion and the targeted enzyme’s process are not clear. This article analyzes the difference in sugar metabolism between tumor cells and normal cells, specifically summarizes and analyzes the inhibitory effect mechanism of pyruvate kinase and lactate dehydrogenase on tumors, and obtains the conclusion that targeted inhibition of PKM and LDH can inhibit the growth and reproduction of tumor cells. Exploring the inhibition of tumor cell dependence on glucose, studying the glycolysis pathway of tumor cells and targeted drugs inhibiting key enzyme activity can help us further understand the metabolic characteristics and growth mechanism of tumor cells, provide new targets and strategies for tumor treatment, and provide a reference for anti-tumor combination therapy and individualized treatment for patients. However, at present, the research on targeted drug toxicity and side effects has not been solved, and the potential side effects and toxicity are not studied enough. Future research should focus on individualized treatment for patients, pay attention to the differences in the activation degree of glycolysis pathway in tumor cells, and bring better treatment results to tumor patients.